1986
DOI: 10.1063/1.865722
|View full text |Cite
|
Sign up to set email alerts
|

Rayleigh–Taylor stability for a normal shock wave–density discontinuity interaction

Abstract: The solution for the perturbation growth of a shock wave striking a density discontinuity at a material interface is developed. The Laplace transformation of the perturbation results in an equation which has a simple solution for weak shock waves. The solution for strong shock waves may be given by a power series. It is assumed that the equation of state is that of an ideal gas. The four independent parameters of the solution are the ratio of specific heat for each material, the density ratio at the interface,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
123
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(131 citation statements)
references
References 8 publications
8
123
0
Order By: Relevance
“…As the shocks separate away from the interface, their corrugation amplitude will oscillate and decrease in time. This well-known fact was predicted theoretically and observed in experiments/simulations and documented over more than 50 years of research on corrugated shocks, either in shock tubes or, recently, with high-power lasers ( Briscoe & Kovitz 1968;Fraley 1986;Velikovich & Phillips 1996;Wouchuk & Nishihara 1996). For an ideal gas EOS, it can be rigorously proven that the amplitude of those oscillations decreases asymptotically in time as t −3/2 for any shock with finite intensity (Zaidel 1960;Fraley 1986;Wouchuk & Cavada 2004).…”
Section: Linear Perturbation Growth (A) Rippled Shock Dynamics and Gementioning
confidence: 94%
See 1 more Smart Citation
“…As the shocks separate away from the interface, their corrugation amplitude will oscillate and decrease in time. This well-known fact was predicted theoretically and observed in experiments/simulations and documented over more than 50 years of research on corrugated shocks, either in shock tubes or, recently, with high-power lasers ( Briscoe & Kovitz 1968;Fraley 1986;Velikovich & Phillips 1996;Wouchuk & Nishihara 1996). For an ideal gas EOS, it can be rigorously proven that the amplitude of those oscillations decreases asymptotically in time as t −3/2 for any shock with finite intensity (Zaidel 1960;Fraley 1986;Wouchuk & Cavada 2004).…”
Section: Linear Perturbation Growth (A) Rippled Shock Dynamics and Gementioning
confidence: 94%
“…The Richtmyer-Meshkov instability (RMI) was predicted by Richtmyer more than 50 years ago; since then it has attracted the attention of scientists worldwide because of its importance in different scenarios (Richtmyer 1960;Meshkov 1969;Fraley 1986;Holmes et al 1999;Zabusky 1999;Velikovich et al 2000Velikovich et al , 2007. Richtmyer studied the problem numerically for a planar shock refracted normally at a contact surface separating two different ideal gases, assuming that the material interface had an initial sinusoidal corrugation.…”
Section: Introductionmentioning
confidence: 99%
“…2 Besides, numericists and experimentalists addressed the effect of shock proximity by using empirical corrections to the impulsive growth rate. [3][4][5] More complex, semianalytical studies have taken into account all relevant phenomena 6,7 and showed good agreement with numerical results obtained by linearizing the Euler equations between the perturbed interface and transmitted/reflected waves, 8 and with the linear interaction analysis at low Atwood numbers of Griffond. 9 In what follows, by modeling the proximity of the receding transmitted and reflected shocks, the analysis in Sec.…”
Section: Introductionmentioning
confidence: 54%
“…This latter ratio can be greater than unity in the heavy region 1 when the incident shock Mach number M I is very high but remains less than 10 as long as A + is not too close to unity and the incident shock is not too strong. For example, in the case of a "light air→ heavy SF 6 " shock interaction at M I = 8.0, whose Atwood number A + Ӎ 0.7 is quite high ͑1:5 density ratio͒ in the heavy region ⌬W / a 1 Ӎ 4.2.…”
Section: A General Formulationmentioning
confidence: 99%
See 1 more Smart Citation